PPD-induced monocyte mitochondrial damage is associated with a protective effect to develop tuberculosis in BCG vaccinated individuals : a cohort study (2017)
ABSTRACT: Introduction: The mechanisms of mononuclear phagocyte death have been associated with the permissiveness and resistance to mycobacterial replication, but it remains unknown whether or not they help predict the risk of developing TB. Objective: To describe the factors associated with the induction of monocyte mitochondrial and membrane damage in response to PPD as well as determine if this type of damage might predict the susceptibility of developing active tuberculosis in a cohort of household contacts (HHCs) from Medellin, Colombia from 2005 to 2008. Methods : The prospective cohort study contains 2060 HHCs patients with pulmonary tuberculosis who were meticulously followed for two years. A survey of the socio-demographic, clinical, epidemiological factors and blood samples were collected. Mononuclear cell cultures were stimulated with or without PPD and the type of monocyte death was determined by the flow of cytometry, an indicator was also used for its analysis. Logistic regression was adjusted by the Generalized Estimations Equations and the survival was estimated with the Kaplan-Meier and Cox regression. Confidence intervals were used for estimating the association. Results : 1,859 out of 2,060 blood samples of the HHCs patients analyzed showed monocyte death. In response to PPD, 83.4% underwent mitochondrial damage while 50.9% had membrane damage. The membrane damage in response to PPD was higher in children under 4 years (OR: 1.57; (95% CI: 1.1 to 2.4) and the HHCs who slept regularly in the same household has an index case of (OR: 1.54; 95% CI: 1.0 to 2.3). After adjustment by age, comorbidities, nutritional status, proximity to index case and overcrowding, the risk of developing active TB among BCG vaccinated HHCs individuals with induction of mitochondrial damage was HR = 0.19 (95% CI: 0.1 to 0.5). Conclusions: The induction of monocytes mitochondrial damage by PPD stimulation correlates with protection of TB disease development in BCG-vaccinated HHCs. This represents a potential tool to predict susceptibility of developing active disease in this population.